Changes in expressions of UDP-glucuronosyltransferases in placenta and fetal liver of rats before birth induced by maternal exposure to bisphenol A during pregnancy - Peili WANG; Jun WANG; Yichen ZHAO; Panjie WANG; Mingyue MA; Zhiwen DUAN; Xiucong PEI; Haiyang YU (环境与职业医学)
BackgroundMaternal exposure to bisphenol A (BPA) during pregnancy is closely related to adverse growth and development conditions such as preterm birth and low birth weight, but the relevant mechanisms are still unclear. UDP-glucuronosyltransferases (UGTs) can regulate the excretion of BPA conjugating with glucuronic acid through urine, which is one of the important pathways for BPA elimination. ObjectiveTo explore the changes in the expression of UGTs in placenta and fetal liver of rats before birth induced by maternal exposure to BPA during pregnancy. MethodsThirty SPF-grade healthy SD pregnant rats were randomly divided into five groups: control group, 0.05, 0.5, 5, and 50 mg·kg−1 BPA groups. The pregnant rats were exposed to BPA dissolved in corn oil via oral gavage daily from gestational day (GD) 5 to GD 19. After anesthesia, the pregnant rats were sacrificed on GD 20 and the placentas were collected. Body length, tail length, and weight of the fetal rats were measured. Fetal liver tissues were then separated, and organ weights were measured. Real-time quantitative polymerase chain reaction (RT-PCR) and Western blot (WB) were used to determine the mRNA and protein levels of UGT1A1, UGT1A6, UGT1A9, and UGT2B1 in the placenta and fetal liver tissues in each group. ResultsThere were no differences in body length and tail length of the pups after maternal exposure to BPA during pregnancy. The fetal body weight and placenta weight in the 5 and 50 mg·kg−1 BPA groups and the liver weight in the 5 mg·kg−1 BPA group reduced compared with the control group (P<0.05). The results of UGTs expressions in placenta showed that compared with the control group, the UGT1A1 mRNA levels in placenta of the BPA groups (exposure dose≥0.5 mg·kg−1) and the UGT1A1 protein level in placenta of the 50 mg·kg−1 BPA group increased (P<0.05); the UGT1A6 mRNA and protein levels in placenta of each BPA group did not change (P>0.05); the UGT1A9 mRNA level in placenta of the 50 mg·kg−1 BPA group and the UGT1A9 protein levels in placenta of the BPA groups (exposure dose≥0.5 mg·kg−1) reduced (P<0.05); while the levels of UGT2B1 mRNA in placenta of the BPA groups (exposure dose≥0.5 mg·kg−1) reduced (P<0.05). The results of UGTs expressions in fetal liver showed that compared with the control group, the UGT1A1, UGT1A6, UGT1A9, and UGT2B1 mRNA levels of each BPA group increased (P<0.05); no obvious alternation was observed in UGT1A6 protein levels in each BPA group (P>0.05); the relative protein levels of UGT1A9 in fetal liver in the 50 mg·kg−1 BPA group increased (P<0.05); conversely, the relative protein levels of UGT2B1 in fetal liver in the BPA groups (exposure dose≥0.5 mg·kg−1) reduced (P<0.05). ConclusionMaternal exposure to BPA during pregnancy can elevate the UGT1A1 gene and protein expressions, inhibit the UGT1A9 gene and protein expressions and UGT2B1 gene expressions in placenta. Besides, maternal exposure to BPA during pregnancy can raise the gene expressions of UGT1A1, UGT1A6, UGT1A9, and UGT2B1 in fetal liver, as well as the protein expression of UGT1A9, but inhibit the protein expression of UGT2B1. These changes may contribute to fetal developmental abnormalities after maternal exposure to BPA during pregnancy.